2017
DOI: 10.1177/0892705717697777
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and thermal stability of polypropylene composites filled with graphene nanoplatelets

Abstract: The thermal properties and thermal stability of polypropylene (PP) composites separately filled with graphene nanoplatelets (GNPs) with three different sizes were measured using a differential scanning calorimetry and a thermal gravimetric analyser. The results showed that the values of the melting temperature of the composites were higher than that of the unfilled PP; the thermal stability increased with increasing the weight fraction and lateral dimension of GNPs in the case of low filler concentration, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The residue amounts were about the weight fractions of GNP which clearly means that the GNP was not burnt off at the temperatures below 600°C as a result of the inert atmosphere [26]. This is similar to the research study of Liang et al [27] who stated the residues found in PP/GNP composites were mainly the GNP.…”
Section: Resultssupporting
confidence: 78%
“…The residue amounts were about the weight fractions of GNP which clearly means that the GNP was not burnt off at the temperatures below 600°C as a result of the inert atmosphere [26]. This is similar to the research study of Liang et al [27] who stated the residues found in PP/GNP composites were mainly the GNP.…”
Section: Resultssupporting
confidence: 78%
“…Two different types of composites were prepared with unmodified (u-GNP) and modified GNPs (PGMA-GNP). A small amount of graphene can significantly improve the mechanical, electrical, and thermal properties of polymer composite materials [26]. Therefore, GNPs were dispersed into the epoxy matrix in 0.1, 0.3, 0.5, 1.5, and 2.0 wt% by using a mechanical stirrer and ultrasonic bath at 60 °C for 1 h. After dispersion, the curing agent (30 wt%) and accelerator (1.0 wt%) were added.…”
Section: Composite Preparationmentioning
confidence: 99%
“…Graphene, as a monolayer of carbon atoms arranged in a honeycomb network, has recently attracted tremendous attention in the fields of fundamental and applied due to its outstanding physical, chemical, and mechanical properties. 1 5 The discovery of new nanomaterial graphene by Andre Geim 6 in 2004 with its unique properties has created a new class of polymer nanocomposites and expanded the application of polymers. 7 Polymers have an important role in the industrial applications, but the increasing demand of materials for advanced applications cannot be provided by simple homopolymers.…”
Section: Introductionmentioning
confidence: 99%